2001
DOI: 10.1074/jbc.m101379200
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Major Glycoproteins of Pigeon Egg White

Abstract: Ovotransferrin (POT), two ovalbumins (POA(hi) and POA(lo)), and ovomucoid (POM) were isolated from pigeon egg white (PEW). Unlike their chicken egg white counterparts, PEW glycoproteins contain terminal Gal␣1-4Gal, as evidenced by GS-I lectin (specific for terminal ␣-Gal), anti-P 1 (Gal␣1-4Gal␤1-4GlcNAc␤1-3Gal␤1-4Glc␤1-1Cer) monoclonal antibody, and P fimbriae on uropathogenic Escherichia coli (specific for Gal␣1-4Gal). Gal␣1-4Gal on PEW glycoproteins were found in N-glycans releasable by treatment with glycoa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
29
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 62 publications
2
29
1
Order By: Relevance
“…We also confirmed that the putative chicken ␣4GalT(Gal), which was identified from chicken genome/protein data bases in NCBI, acts as a Gb3 synthase, like human ␣4GalT(Gal). This observation is consistent with the absence of Gal␣1-4Gal on glycoproteins in chicken (4,25). The high similarity between pigeon ␣4GalT(Gal) and chicken Gb3 synthase implies that they are most likely derived from a common ancestral gene relatively recently.…”
Section: Pigeon ␣4galt(gal) Possesses Distinct Substrate Preferences supporting
confidence: 77%
See 3 more Smart Citations
“…We also confirmed that the putative chicken ␣4GalT(Gal), which was identified from chicken genome/protein data bases in NCBI, acts as a Gb3 synthase, like human ␣4GalT(Gal). This observation is consistent with the absence of Gal␣1-4Gal on glycoproteins in chicken (4,25). The high similarity between pigeon ␣4GalT(Gal) and chicken Gb3 synthase implies that they are most likely derived from a common ancestral gene relatively recently.…”
Section: Pigeon ␣4galt(gal) Possesses Distinct Substrate Preferences supporting
confidence: 77%
“…Mammals express Gal␣1-4Gal on glycolipids, such as globotriosylceramide (Gb3, 2 Gal␣1-4Gal␤1-4Glc-Cer) and P 1 antigen (Gal␣1-4Gal␤1-4GlcNAc␤1-3Gal␤1-4Glc-Cer), but not on glycoproteins, except for those found in hydatid fluids caused by tapeworm (5,6). In contrast, we found that pigeon egg white is a rich source of glycoproteins that possess the Gal␣1-4Gal␤1-4GlcNAc sequence at the nonreducing termini of N-glycans (4). It was demonstrated that pigeon egg white glycoproteins are useful in preventing infection with uropathogenic E. coli (7).…”
contrasting
confidence: 43%
See 2 more Smart Citations
“…When P-fimbriated E. coli were allowed to accumulate on pigeon ovalbumin, a Gal-1,4-Gal-presenting glycoprotein (27,28), for 5 min at shears ranging from 0.01 to 4.3 pN/m 2 ( Fig. 7A), no shear threshold was seen, and accumulation decreased with increased shear.…”
Section: Shear Stress Enhances P-fimbrial E Coli Adhesion To Gal-14mentioning
confidence: 99%